Prognostic value of residual cancer burden after neoadjuvant chemotherapy in breast cancer: a comprehensive subtype-specific analysis - Soo-Young Lee; Tae-Kyung Yoo; Sae Byul Lee; Jisun Kim; Il Yong Chung; Beom Seok Ko; Hee Jeong Kim; Jong Won Lee; Byung Ho Son (Scientific Reports)
Abstract This study evaluated the prognostic impact of residual cancer burden (RCB) on breast cancer subtypes following neoadjuvant chemotherapy (NAC). We retrospectively examined 2,416 breast cancer patients treated with NAC and surgery at Asan Medical Center (2015–2020). Baseline characteristics, clinicopathological parameters, recurrence, and survival outcomes were analyzed using Kaplan-Meier and Cox regression methods to assess RCB’s prognostic significance across subtypes. Pathologic complete response (pCR) was achieved in 25.6% (619) of patients. RCB2 was the most common (44.0%, 1,063), followed by RCB3 (19.6%, 474) and RCB1 (10.8%, 260). Among HR-/HER2 + patients, 67% had RCB0/1, while 87% of HR+/HER2- patients had RCB2/3. Higher RCB was significantly associated with worse overall survival (OS) and disease-free survival (DFS) across all subtypes. Subtype-specific analysis revealed that HR-/HER2 + patients with RCB3 and HR-/HER2- patients with RCB2/3 had significantly worse OS and DFS. Multivariate analysis revealed that RCB2/3 (vs. RCB0), total mastectomy (vs. breast-conserving surgery), axillary lymph node dissection (ALND), lymphovascular invasion (LVI), high Ki-67 index (≥ 20), HR negativity, and HER2 negativity were linked to higher risks of recurrence and death (p < 0.05). Factors associated with higher RCB included ALND, LVI, higher Ki-67, and HR+/HER2- subtype. RCB classification is a strong prognostic indicator across all subtypes. Patients with RCB2/3 in the HR-/HER2- and RCB3 in the HR-/HER2 + subtypes had particularly poor outcomes, suggesting benefits from additional treatments beyond standard care.